Efficacy and safety of PI3K inhibitors combined with fulvestrant for HR+/HER2− advanced breast cancer: a systematic review and meta-analysis - Li, Xuefeng; Wang, Hongxian; Lin, Shuhui; Chen, Tianwen (Frontiers in Oncology, 2025)
ObjectivesThis systematic review and meta-analysis aimed to evaluate the efficacy and safety of combination of Phosphatidylinositol 3-kinase (PI3K) inhibitors and fulvestrant in patients with advanced breast cancer (ABC) who are hormone receptor-positive (HR+) and human epidermal growth factor receptor 2-negative (HER2-).MethodsA systematic search was conducted across the PubMed, Cochrane Library, EMBASE databases and major conference websites (ASCO, ESMO, SABCS) to identify randomized controlled trials (RCTs) evaluating the combination of PI3K inhibitors and fulvestrant in the treatment of advanced breast cancer. Two independent reviewers systematically screened the literature, extracted data, and assessed the risk of bias for the included studies based on predefined criteria. Meta-analysis was subsequently performed using R software in accordance with the PRISMA guidelines.ResultsA total of five randomized controlled trials (RCTs) involving 3,011 patients were included. The findings indicated that the combination of PI3K inhibitors and fulvestrant significantly improved progression-free survival (PFS) (HR = 0.74, 95% CI 0.67-0.80, P < 0.0001) and the objective response rate (ORR) (RR = 1.80, 95% CI: 1.39-2.35, P < 0.0001) compared to placebo plus fulvestrant. However, there was no statistically significant difference in clinical benefit rate (CBR) (RR = 1.10, 95% CI: 0.97-1.25, P = 0.1341). Subgroup analysis indicated that the predefined subgroup of PFS based on PIK3CA mutation status assessed by ctDNA was statistically significant (P = 0.0039), whereas the predefined subgroup of PFS based on PIK3CA mutation status assessed by tumor tissue was not statistically significant (P = 0.1514). In terms of adverse events, the incidence of grade ≥3 events was significantly increased in the PI3K inhibitors combined with fulvestrant group (RR=2.11, 95% CI: 1.73-2.58, P<0.0001), particularly hyperglycemia, rash, and transaminitis (ALT).ConclusionThe combination of PI3K inhibitors and fulvestrant significantly improved PFS and ORR in patients with advanced breast cancer. However, substantial dose-limiting toxicities associated with this therapeutic regimen restrict its broader clinical application. In patients with PIK3CA mutations detected on ctDNA analysis, PFS was significantly improved compared to those with wild-type PIK3CA, suggesting that ctDNA-based PIK3CA mutation status may serve as a potential biomarker for treatment response.Systematic review registrationPROSPERO, identifier CRD42023407466.